As Historical Subjects: The African Diaspora in Colonial Latin American History. Issue 12 (December 2013) - O'Toole, Rachel Sarah
Abstract This article celebrates and explores the current historiography on colonial Afro‐Latin Americans in the Spanish Americas to illuminate how scholars can continue to develop their methodological approaches to recuperating enslaved and free agency. Drawing on Michel‐Rolph Trouillot's distinction between historical actors and purposeful subjects, the essay suggests that even within slavery, men and women of African descent were able to contest slaveholding, develop their own standards within racial hierarchies, claim subject positions as Catholics, and lay claim to freedom. By asking questions regarding African‐descent defined objectives, scholars have begun to allow Africans and their descendants to articulate interior selves.